Hepcidin as a new biomarker for detecting autologous blood transfusion. Issue 5 (6th April 2016) - Leuenberger, Nicolas; Barras, Laura; Nicoli, Raul; Robinson, Neil; Baume, Norbert; Lion, Niels; Barelli, Stefano; Tissot, Jean‐Daniel; Saugy, Martial
Abstract : Autologous blood transfusion (ABT) is an efficient way to increase sport performance. It is also the most challenging doping method to detect. At present, individual follow‐up of haematological variables via the athlete biological passport (ABP) is used to detect it. Quantification of a novel hepatic peptide called hepcidin may be a new alternative to detect ABT. In this prospective clinical trial, healthy subjects received a saline injection for the control phase, after which they donated blood that was stored and then transfused 36 days later. The impact of ABT on hepcidin as well as haematological parameters, iron metabolism, and inflammation markers was investigated. Blood transfusion had a particularly marked effect on hepcidin concentrations compared to the other biomarkers, which included haematological variables. Hepcidin concentrations increased significantly: 12 hr and 1 day after blood reinfusion, these concentrations rose by seven‐ and fourfold, respectively. No significant change was observed in the control phase. Hepcidin quantification is a cost‐effective strategy that could be used in an "ironomics" strategy to improve the detection of ABT. Am. J. Hematol. 91:467–472, 2016. © 2016 Wiley Periodicals, Inc.